Prevalence of Endometriosis During Abdominal or Laparoscopic Hysterectomy for Chronic Pelvic Pain. Issue 10 (October 2016) - Mowers, Erika L.; Lim, Courtney S.; Skinner, Bethany; Mahnert, Nichole; Kamdar, Neil; Morgan, Daniel M.; As-Sanie, Sawsan
Abstract : (Abstracted from Obstet Gynecol 2016;127:1045–1053) Chronic pelvic pain is common in reproductive-aged women. A large number of women with chronic pelvic pain or endometriosis undergo hysterectomy: 10% to 32% for chronic pelvic pain and 5% to 19% for endometriosis.